GAMBARAN KEPATUHAN DIET PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA RAWAT JALAN DI RSUD KAYEN KABUPATEN PATI TAHUN 2015 THE DESCRIPTION OF THE DIETARY PURSUANCE CRONICAL RENAL FAILURE PATIENTS UNDERGOING HEMODIALYSIS OUTP - Susatyo, Bambang (Jurnal Kesehatan Masyarakat (e-Journal), 2016)
Dietary therapy is one very important factor in the management of patients with chronic renal failure by hemodialysis. Compliance in implementing the diet be hope for hospital medical team. The study aims to describe dietary compliance of patients with chronic renal failure undergoing hemodialysis outpatients in hospitals Pati Kayen 2015. exploratory research using qualitative method by conducting in-depth interviews. The samples were all patients with chronic renal failure undergoing hemodialysis outpatients in 2015, amounting to 8 respondents.        The survey results revealed that image data obtained demographic characteristics of the majority of respondents are male ( 62.5 % ) , respondents aged 45-50 years ( 75 % ) , final Education Junior High School ( 50 % ) , working as farm laborers ( 62.5 % ) , adherence to the diet ( 75 % ) and undergoing hemodialysis duration > 12 months ( 75 % ) . BMI calculation results obtained 5 people (62.5%) of respondents are in the category of malnutrition , results of laboratory data obtained six respondents or 75% levels ureumnya 40.1 to 100 mg / dl or above the normal range. And 4 respondents or 50% of blood creatinine levels of 5,1- 10 mg / dl or above the normal range.       Especially for Dietician on the Nutrition Installation Kayen Pati Regency Hospital to provide the time and schedule for nutritional counseling for patients with chronic renal failure undergoing hemodialysis outpatients in order to maximize the expected results.